Do men and women respond differently to Sharia marketing? Exploring ethical drivers of loyalty in Islamic banking - Hadi, Solikhul; Rumanto, Agep (Journal of Islamic Economics Lariba, 2026)
IntroductionEthical and Sharia-compliant marketing has become a strategic foundation for Islamic banks seeking to build sustainable customer loyalty. Unlike conventional marketing, Sharia marketing emphasizes honesty, fairness, and trust, reflecting Islamic ethical values in every business transaction. However, the extent to which these ethical marketing practices drive customer loyalty—and whether gender differences influence these effects—remains underexplored.ObjectivesThis study aims to analyze the impact of Sharia marketing ethics, represented by the five dimensions of the Islamic marketing mix (product, price, promotion, people, and place), on customer loyalty in Islamic banking. It further examines the moderating role of gender in these relationships to uncover differential behavioral responses among male and female customers.MethodA quantitative explanatory approach was employed, collecting survey data from 295 customers of Bank Syariah Indonesia (BSI) using purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.2.9 to assess both direct and moderating effects. The model’s validity and reliability were confirmed through confirmatory factor analysis and multicollinearity diagnostics.ResultsFindings reveal that all five elements of Sharia marketing ethics significantly influence customer loyalty, with promotion, product, and place showing the strongest positive effects. Interestingly, the “people” dimension has a negative influence, indicating that employee interactions do not always align with customers’ ethical expectations. Gender significantly moderates the relationships between price, promotion, people, and place with loyalty, suggesting that male and female customers respond differently to ethical marketing signals.ImplicationsThe results underscore the importance of integrating ethical and gender-sensitive strategies in Islamic marketing. Islamic banks should focus on authentic communication, fair pricing, and improving service interactions to strengthen customer trust and long-term loyalty. These insights also provide policy implications for enhancing the ethical governance of marketing practices in Islamic financial institutions.Originality/NoveltyThis study contributes to Islamic marketing literature by integrating ethical Sharia marketing principles with gender-based behavioral analysis. It offers a novel perspective by demonstrating how gender moderates the ethical marketing–loyalty relationship, providing both theoretical enrichment and practical guidance for inclusive marketing strategies in Islamic banking.